The Challenges of Online Assessment During the Covid-19 Pandemic: Case Study: Romania - Anamaria –Mirabela POP; Monica-Ariana SIM (Communications of International Proceedings, 2021)
When the COVID-19 pandemic started, higher education, like all other industries, was affected. Institutions around the world have experienced an almost sudden shift to online learning in an effort to slow the spread of the disease. Multiple challenges arose, how does one go from a physical classroom to a multi panel Zoom window, how do you balance real-time teaching with asynchronous learning and how do you support faculty and students along the way? Educators started searching for tips and many universities and organizations have gathered resources to move courses online. When physical lectures were replaced by online conferences and weblectures, the next issue to be addressed was student assessment. There have been growing concerns with improving assessment practices in higher education across the world, considering the fact that appropriate assessment methods play a vital role in achieving the goal of education in any county. In the vast literature on education, so much is really written around the same concepts, that if you read an article or a book you have the impression that you have understood what all is about. Yet, things are slightly more complicated, though. In this paper, we will make a presentation of the relation between the basic actions of the educational process: teaching, learning and assessment and the challenges that world education systems faced in the last year, since the outbreak of COVID-19 pandemic. The paper tackles the steps that have been taken and the solutions provided by the online technology to the education systems in order to cope with the quality standards that these universities, schools and other institutions set for themselves.
Keywords: Assessment; Online Assessment; Digital Platforms; COVID-19; Romania.